Innovations in osteomyelitis research: A review of animal models - Roux, Kylie M. (Animal Model Exp Med, 2021)
Infection of bone tissue, or osteomyelitis, has become a growing concern in modern healthcare due in no small part to a rise in antibiotic resistance among bacteria, notably Staphylococcus aureus. The current standard of care involves aggressive, prolonged antibiotic therapy combined with surgical debridement of infected tissues. While this treatment may be sufficient for resolving a portion of cases, recurrences of the infection and associated risks including toxicity with long‐term antibiotic usage have been reported. Therefore, there exists a need to produce safer, more efficacious options of treatment for osteomyelitis. In order to test treatment regimens, animal models that closely mimic the clinical condition and allow for accurate evaluation of therapeutics are necessary. Establishing a model that replicates features of osteomyelitis in humans continues to be a challenge to scientists, as there are many variables involved, including choosing an appropriate species and method to establish infection. This review addresses the refinement of animal models of osteomyelitis to reflect the clinical disease and test prospective therapeutics. The aim of this review is to explore studies regarding the use of animals for osteomyelitis therapeutics research and encourage further development of such animal models for the translation of results from the animal experiment to human medicine.